PENYELESAIAN MASALAH PROGRAM LINIER FUZZY DENGAN BILANGAN FUZZY MENGGUNAKAN METODE SABIHA LINEAR REAL - Eky Pawestri Gita Asmara (MATEMATIKA FSM, UNDIP, 2016)
ABSTRACT. Fuzzy Linear Programming (FLP) is one form of a linear programming that includes fuzzy numbers. Several methods have been developed to solve the FLP problems, one of which Sabiha’s Methods. The method is modifying Two Phase Methods such that it can be used in the FLP. Modification is done by changing the general form to be adjusted with the